KEMITRAAN ANTARA PEMERINTAH KOTA BOGOR DENGAN SWASTA DALAM PENATAAN DAN PEMELIHARAAN TAMAN TAHUN 2013-2016 - Kahfi Dwi Septian; Kushandajani .; Puji Astuti (Journal of Politic and Government Studies, 2016)
The issue of green space, especially parks, often found in big cities in Indonesia. The existence of the city park is often underestimated, because they are considered to have a smaller financial value compared to other assets (such as buildings, infrastructure, roads, etc), when in reality the cost required for the maintenance of the park is quite large. That prompted the Government of Bogor City to cooperate with PT. Pilar Hijau Madani in structuring and maintaining the city parks. This study used qualitative research methods and the data was collected through observation, interviews, documentation and literature. The subjects of this study are Department of Hygiene & Landscaping of Bogor City and PT. Pilar Hijau Madani. The purpose of this study was to determine the application of the partnership between the Government of Bogor City and PT. Pilar Hijau Madani in structuring and maintaining the city park, and also to find out any obstacles thay may arise in estabilishing a partnership between the two sides. This agreement using lease contracts model with several elements in fit, including: 1) PT. Pilar Hijau Madani as the party that partnered in the arrangement and maintaining of the city park; 2) The objects of the partnership are Taman Air Mancur dan Taman Pulau across the Pangrango Plasa; 3) PT. Pilar Hijau Madani is responsible for the entire cost of the arrangement and maintaining of the park; 4) As the compensation,PT. Pilar Hijau Madani was given the permission to put up billboards in the parks area. The result of this study suggest several reason that encourage partnerships between government and the private sectors, such as: 1) as an alternative source of financing for regional development; 2) as a form of contribution of the private sector in regional development; 3) the involvement of the private sector in regional development is a way to encourage the private sector in order to contribute to the acceleration of development.Key Words: Public Private Partnership, Park